VD_FINDINFO Faillite / 2014 / 28 vom 28. August 2014 - VD Tribunal cantonal (2014)
OUVERTURE DE LA FAILLITE, ACTE DE RECOURS, MOTIF DU RECOURS, CONDITION DE RECEVABILITÉ | 174 al. 1 LP, 321 al. 1 CPC (CH)